Pneumonia caused by SARS-COV-2: diagnosis and treatment in outpatient settings - Melnyk, V. P.; Panasiuk, O. V.; Sadomova-Andrianova, H. V.; Antoniuk, I. V.; Sliusarchuk, I. O.; Solonynka, H. Ya. (Zaporozhye Medical Journal, 2021)
The aim of the study was identifying the features of infection in the site, clinical course of the disease, amount and frequency of patient examinations, family doctor communications and treatment of patients with pneumonia caused by SARS-Cov2. Materials and methods. We examined 23 families of 2–6 members (a total of 78), among them 41 patients with SARS-COV-2 pneumonia. The amount of patient examination (PCR, plain X-ray and CT of the thoracic cavity, coagulogram, blood oxygen saturation) and treatment extent (antibacterial, anticoagulant and oxygen therapy) were considered. Results. The contagiousness of the disease in the families of patients was from 33 % to 100%. The thoracic CT overuse: 73.3 % repeated, 33.0 % triple. Family doctors monitored the treatment only in 14.6 % of cases. The antibacterial therapy administration was 2 times more often than necessary; the treatment was changed by patients themselves or their acquaintances. A hospitalization was offered to patients with a decreased blood oxygen saturation of 92 % and below (29.3 %), and only 2 patients agreed to it. In a lack of treatment efficacy, the patients used respiratory fluoroquinolones (levofloxacin, moxifloxacin), meropenem, linezolid, amikacin, which are among the main drugs for the treatment of resistant tuberculosis. Extensive misuse of antibacterial drugs unnecessarily will result in an alarming increase in antibiotic-resistant infections after the COVID-19 pandemic. Conclusions. Pneumonia caused by SARS-COV-2 is a highly contagious disease in a family cluster (33–100 %). Routine administration of antibacterial drugs (especially levofloxacin, moxifloxanemine, meropenem, linezolid, amikacin) for patients with suspected SARS-COV-2 pneumonia by thoracic CT or PCR-confirmed without proven need is not only unnecessary, but even dangerous due to the potential increase in resistance to these drugs, which are the primary in the treatment of resistant tuberculosis. The anamnesis of the disease, oxyhemometry and coagulogram are of great importance when examining a patient with this pathology.